2014
DOI: 10.1186/1471-2393-14-270
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to evidence based care practices for childbirth before and after a quality improvement intervention in health facilities of Rajasthan, India

Abstract: BackgroundAfter the launch of Janani Suraksha Yojana, a conditional cash transfer scheme in India, the proportion of women giving birth in institutions has rapidly increased. However, there are important gaps in quality of childbirth services during institutional deliveries. The aim of this intervention was to improve the quality of childbirth services in selected high caseload public health facilities of 10 districts of Rajasthan. This intervention titled “Parijaat” was designed by Action Research & Training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 32 publications
6
53
3
2
Order By: Relevance
“…Our informal observations during data collection – of labour room environments that often appeared chaotic and of some health workers that could be abusive, dominating and threatening on occasions (available from the corresponding author) – were consistent with those previously found in Madhya Pradhesh 46 and Rajasthan 25 . Inadequate knowledge and skills, lack of enabling environments, limited supportive supervision, staffing shortages and the poor quality of in-service training could all be underlying causes of the generally poor quality of maternity care in India 24 , 46 . The Indian government is currently implementing a range of schemes to improve the quality of intrapartum and immediate postpartum care 47 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our informal observations during data collection – of labour room environments that often appeared chaotic and of some health workers that could be abusive, dominating and threatening on occasions (available from the corresponding author) – were consistent with those previously found in Madhya Pradhesh 46 and Rajasthan 25 . Inadequate knowledge and skills, lack of enabling environments, limited supportive supervision, staffing shortages and the poor quality of in-service training could all be underlying causes of the generally poor quality of maternity care in India 24 , 46 . The Indian government is currently implementing a range of schemes to improve the quality of intrapartum and immediate postpartum care 47 .…”
Section: Discussionsupporting
confidence: 76%
“…In a study based in Rajasthan, partograph use was found to be especially weak and monitoring was found often to consist only of repeated unhygienic vaginal examinations 24 . We found active management of the third stage of labour to be more common in the facilities we surveyed than reported in some neighbouring districts of Uttar Pradesh 23 .…”
Section: Discussionmentioning
confidence: 55%
“…The current study is lower than study done in California (74.4%), Iran (78%), Brazil (50%) [13,26,27]. This may be possibly due to cross cultural difference, divided loyalty, self-selection, and limited number of staffs serving in the hospital [28].…”
Section: Discussioncontrasting
confidence: 72%
“…An institution based cross-sectional study from Cameroon found out that age; sex, profession, and experience were associated with evidence based intrapartum care [13][14][15][16]. Several studies have shown that age, sex, profession, qualification, experience, access to internet, workshop, conferences, searching for the Cochrane database, were statistical associated with evidence based practice [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Filler et al [7] also found that critical steps of resuscitation have not being followed and improved education and further training on resuscitation need to be imparted in labor room team [6]. Furthermore, availability of commodities in the newborn care corner for resuscitation is also an important bottleneck found in our surveys such as availability of functional radiant warmer and Ambu bag was approximately 80%; shoulder roll 29%; either availability of mask 0 or 1 was 50%; availability of both masks was 28% [8].…”
Section: Discussionmentioning
confidence: 90%